Instructional Leadership for Strengthening Technology-Responsive Teacher Competence in Deep Learning - Yuniarti, Yuniarti; Herawati, Endang Sri Budi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
The increasing complexity of twenty-first-century education requires school leaders to foster teacher competence that integrates pedagogical innovation with technology-responsive instructional practices to support deep learning. This study synthesizes empirical evidence on the contribution of instructional leadership to strengthening teacher competence for implementing deep learning within contemporary educational contexts. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines by analyzing 16 empirical studies published between 2016 and 2025 and retrieved from Scopus-indexed sources. The selected studies were examined through a thematic synthesis to identify recurring patterns, leadership practices, and professional development strategies that enhance teachers' pedagogical capacity. The findings indicate that instructional leadership plays a pivotal role in developing technology-responsive teacher competence by promoting collaborative professional learning, strengthening academic supervision, facilitating continuous professional development, and encouraging reflective instructional practices. Effective school leaders also support the integration of technology-enhanced pedagogies through coaching, professional learning communities, lesson study, and project-based learning, enabling teachers to design meaningful learning experiences that foster higher-order thinking and student engagement. Furthermore, the review demonstrates that instructional leadership contributes to the creation of sustainable learning ecosystems in which pedagogical innovation and technology integration reinforce the implementation of deep learning. These findings highlight the strategic importance of instructional leadership in advancing technology-responsive teaching practices and provide implications for leadership development programs, teacher professional learning, and educational policies aimed at supporting pedagogical transformation in the digital era.